Algorithm for the provision of comprehensive psychotherapeutic support to women experiencing neuropsychiatric symptoms during rehabilitation following the treatment of malignant neoplasms of the reproductive system - D. V. Blinov; A. G. Solopova; E. E. Achkasov; E. S. Akarachkova; O. V. Kotova; S. A. Akavova; V. N. Galkin; G. K. Bykovshchenko; L. N. Sandzhieva; D. I. Korabelnikov; T. A. Blbulyan; D. A. Petrenko; et al. (Эпилепсия и пароксизмальные состояния)
Background. Radical treatment of malignant neoplasms (MNs) of female reproductive system often has serious consequences. Chronic pain syndrome, distress, anxiety and depression, decreased self-esteem, sexual dysfunction and social maladjustment reduce quality of life (QoL) and require psychotherapeutic support.Objective: to create an algorithm for the provision of comprehensive psychotherapeutic support during rehabilitation following the treatment of reproductive system MNs and to evaluate its effect on QoL indicators in women with neuropsychiatric disorders.Material and methods. The algorithm for the provision of comprehensive psychotherapeutic support included clinical interview, cognitive behavioral therapy, visualization, audio therapy, art therapy, group and individual psychotherapy, family psychotherapy, image therapy. The QoL indicators were determined by questionnaires using the Functional Assessment of Cancer Therapy – General (FACT-G) with nosology-specific extensions (subscales of physical well-being, social/family well-being, emotional wellbeing and functional well-being), Hospital Anxiety and Depression Scale (HADS), Kupperman–Uvarova Modified Menopausal Index (MMI). The follow-up period was 1 year after radical surgical treatment of reproductive system MNs in different localizations. The main group received the algorithm for the provision of comprehensive psychotherapeutic support as part of active medical rehabilitation, the comparison group received basic rehabilitation.Results. The study included 47 women with vulvar cancer (VC): active rehabilitation group (VC-1) – 24 patients and basic rehabilitation group (VC-2) – 23 patients; 61 women with endometrial cancer (EC): active rehabilitation group (EC-1) – 29 patients and basic rehabilitation group (EC-2) – 32 patients; 103 women with cervical cancer (CC): active rehabilitation group (CC-1) – 51 patients and basic rehabilitation group (CC-2) – 52 patients; 62 women with stages I–II ovarian cancer (OC) and low malignant potential tumor (LMPT): active rehabilitation group (LMPT-1) – 29 patients and basic rehabilitation group (LMPT-2) – 33 patients. Differences in physical, social/family and functional well-being (FACT-G) were significant from the 6th month and in emotional well-being – by the end of follow-up. Neurovegetative and psycho-emotional disorders, as assessed by Kupperman–Uvarova MMI, showed significant positive dynamics in women who received the algorithm for the provision of comprehensive psychotherapeutic support, in contrast to the comparison group, where these indicators remained without significant dynamics or worsened by the end of the follow-up period. The HADS scores during psychotherapeutic support decreased to normal values at the 6–12th months of follow-up, while those who received the basic rehabilitation continued to have subclinical anxiety and depression.Conclusion. The developed algorithm for psychotherapeutic support as part of active medical rehabilitation of women who underwent radical treatment for reproductive system MNs (VC, EC, CC, OC, and LMPT) has demonstrated its effectiveness, justifuing its implementation in clinical practice.